A phase 1 study of cetuximab and lapatinib in patients with advanced solid tumor malignancies. Issue 10 (29th January 2015) - Deeken, John F.; Wang, Hongkun; Subramaniam, Deepa; He, Aiwu Ruth; Hwang, Jimmy; Marshall, John L.; Urso, Christina E.; Wang, Yiru; Ramos, Corinne; Steadman, Kenneth; Pishvaian, Michael J.
<x xml:space="preserve">Abstract</x> BACKGROUND Acquired resistance to antiepidermal growth factor receptor (anti‐EGFR) therapy may be caused by EGFR–v‐erb‐b2 avian erythroblastic leukemia viral oncogene homolog 2 (ErbB2) heterodimerization and pathway reactivation. In preclinical studies, inhibiting ErbB2 blocked this resistance mechanism and resensitized cells to anti‐EGFR therapy. Cetuximab targets EGFR, whereas lapatinib inhibits both EGFR and ErbB2. The objective of this phase 1 trial was to assess the safety, dose‐limiting toxicities (DLTs), and maximum tolerated doses (MTDs) of cetuximab and lapatinib in patients with solid tumors. METHODS Patients received standard weekly cetuximab with escalating lapatinib doses of 750 mg, 1000 mg, or 1250 mg daily in 3‐week cycles. DLTs were monitored through the end of cycle 2. Pretreatment and post‐treatment tumor biopsies and germline DNA samples were obtained for correlative studies. RESULTS Twenty‐two patients were enrolled, and 18 patients each were evaluable for toxicity and response. Fifty‐nine percent of patients had received prior anti‐EGFR therapy. Common toxicities included rash and diarrhea. No patient experienced a DLT at the highest dose level, and no grade 4 toxicity was observed. Response included no complete responses, 3 partial responses, 9 patients with stable disease, and 6 patients with disease progression, for an overall response rate of 17% and a clinical benefit rate of 67%. The clinical benefit rate in patients who had previously received anti‐EGFR therapy was 70%. The mean treatment duration was 4.7 cycles (range, 1‐14 cycles). Decreased expression of EGFR/ErbB2 pathway components after treatment was correlated with response, whereas increased expression in the PI3K, Jak/Stat, and MAPK pathways occurred in nonresponders. CONCLUSIONS The combination of cetuximab and lapatinib was well tolerated, had the expected toxicities, and exhibited notable clinical activity, including in patients who had received previous anti‐EGFR therapy. Further clinical study of this combination is warranted. Cancer 2015;121:1645–1653. © 2015 American Cancer Society.